Efficacy of an Objective Structured Clinical Examination Training Approach for Training Pharmacy Students in Diabetes Mellitus Counseling: A Randomized Controlled Trial - Imaneh Farahani; Samieh Farahani; Maira A. Deters; Holger Schwender; Stephanie Laeer (Pharmacy, 2020)
Pharmacists’ tasks are multifaceted and include, for example, vital counseling and communication skills. Objective Structured Clinical Examinations (OSCEs) could be used to train pharmacy students in these skills. Our study sought to determine the efficacy of our OSCE training approach for training pharmacy students’ counseling and communication skills on diabetes mellitus compared to a control group. This randomized controlled study was conducted with pharmacy students using a pre-post-design. The intervention group completed diabetes OSCE training, while the control group solved diabetes patient cases using subjective, objective, assessment, and plan notes. Before and after the respective training, both groups completed OSCEs evaluating counseling and communication skills. Before each OSCE encounter, the participants completed a self-assessment questionnaire and, upon completion of the seminar, filled out a satisfaction survey. The OSCE-trained group demonstrated a significantly greater increase in counseling and communication skills and self-confidence than the control group. Both groups were generally satisfied with the seminar. These results demonstrate that our OSCE training approach allows for the effective training of pharmacy students’ diabetes counseling and communication skills and suggests the inclusion of such a skill-based approach more widely in pharmacy students’ education.